Description of a new species of the genus Paraedes (Diptera: Culicidae) in Assam, India - Natarajan, R. (Zootaxa, 2019)
A new species, Paraedes jambulingami, is described from Assam, northeastern India. The adult male and female are described in detail and an illustration of the male is provided. This species is easily distinguished from all known species of the genus Paraedes by the presence of broad silvery or golden scales on the paratergite and the outer arm of the basal mesal lobe of the male genitalia bearing a long, flattened blade-like seta. Dichotomous keys are provided for the identification of the adult females and males of the five species of the genus that are known to occur in India.